Lead‐Free Chiral 2D Double Perovskite Microwire Arrays for Circularly Polarized Light Detection. Issue 3 (6th December 2021) - Zhao, Yingjie; Dong, Meiqiu; Feng, Jiangang; Zhao, Jinjin; Guo, Yangwu; Fu, Yue; Gao, Hanfei; Yang, Junchuan; Jiang, Lei; Wu, Yuchen
Abstract: The realization of polarized photodetection vigorously accelerates the development of applications in quantum communication, medicine, imaging, and sensing. Polarized light detection has been realized based on chiral perovskites, but the high concentrations of toxic lead and instability in those reported perovskites impose difficulties for their commercial applications. Furthermore, the precise patterning of perovskite arrays with high crystallinity is in high demand for the integration of optoelectronic devices. Herein, pure (001)‐orientated lead‐free chiral 2D double perovskite single‐crystalline microwire arrays are fabricated by the capillary‐bridge confined assembly technique. Perovskite microwire arrays present remarkable environmental stability under ambient conditions. With the synergy of the excellent crystallinity and sensitive circular‐polarization absorption of chiral perovskite microwire arrays, outstanding circularly polarized light photodetectors are realized, with responsivity exceeding 52 mA W −1 and detectivity exceeding 3.9 × 10 11 Jones. Abstract : Pure (001)‐orientated lead‐free chiral 2D double perovskite single‐crystalline microwire arrays are realized by employing the capillary‐bridge assembly technique. Perovskite microwire arrays present remarkable environmental stability under ambient conditions. Microwire arrays integrate excellent crystallinity and sensitive circular‐polarization absorption, yielding outstanding circularly polarized light photodetectors with responsivity exceeding 52 mA W −1 and detectivity exceeding 3.9 × 10 11 Jones.